Faktor Risiko Infeksi Bakteri Penghasil Extended Spectrum Beta-Lactamase (ESBL) pada pasien ICU di RS Jogja Tahun 2023 - Kian Sinanjung; Fatrinawati; Istiqomah; Gita Mayasari (Infomasi dan Promosi Kesehatan, 2024)
INTRODUCTION Infection by Extended Spectrum Beta-Lactamase (ESBL)-producing bacteria in Intensive Care Unit (ICU) is associated with treatment failure, prolonged hospital stay, increased costs and patient mortality. The factors of infection by ESBL-producing bacteria are important to figure out so that prevention and control efforts can be made. The aim of the study is to understand the risk factors associated with ESBL-producing bacteria infections in ICU of Jogja Hospital. METHOD This retrospective case control study included ICU’s patients who have an infection with confirmed E. coli or K. pneumoniae based on microbiological examination from January-December 2023. The patient’s data were obtained from the medical record to find the risks factors. Cases were defined as E. coli or K. pneumoniae ESBL, while controls were defined as non ESBL E. coli or K. pneumoniae. Data were analyzed using SPSS version 25. Bivariate analysis was carried out on independent variables (sex, age, length of hospitalization, comorbidity, cephalosporin usage, duration of antibiotic, utilization of urinary catheter and central venous catheter, exposure to mechanical ventilation, and presence of open wounds). Risk factors with P values <0.25 on bivariate analysis were included in multivariate logistic regression analysis. Two-sided P values less than 0,05 were considered statistically significant. RESULT Based our findings, there were 30 patients with ESBL-producing E. coli or K. pneumoniae (cases) and 32 patients with non ESBL-producing E. coli or K. pneumoniae (controls). P value <0.05 is the presence of open wounds. Based on multivariate analysis in table 3, the presence of open wounds has statistical significance, OR 6.52 (IK 95% p = 0.011). CONCLUSION The presence of open wounds is associated with the occurrence ESBL-producing E. coli or K. pneumoniae infection in ICU of Jogja Hospital.